Professionalism of Teachers In Enhancing Students’ Learning Motivation at MTs Al-Mahrusiyyah Lirboyo - Zuhri, Syaifudin (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2024)
This study aims to analyze the professionalism of teachers in improving students’ learning motivation at MTs. Al-Mahrusiyyah Lirboyo Kediri. This research uses a qualitative descriptive approach, with data collected through observation, interviews, and documentation. The findings indicate that teacher professionalism is reflected in four main competencies: pedagogical, personal, social, and professional. These competencies significantly contribute to enhancing students’ learning motivation. Teachers at MTs. Al-Mahrusiyyah implement varied learning strategies, emphasize a humanistic approach, and create participatory and meaningful learning environments. Field data show that teachers’ skills in building empathetic communication and providing positive reinforcement play a crucial role in sustaining students’ enthusiasm. This study concludes that improving teacher professionalism directly impacts the quality of instruction and students’ motivation, particularly in a pesantren-based educational setting.